Library and Information Services and Security Challenges in Two Selected Academic Libraries in Southeast Nigeria - Oguedoihu, Julia Chinwe; Adinchezor, Ifeyinwa Patience (Ghana Library Journal, 2022)
This paper investigated library and information services and security challenges in two selected academic libraries in South East, Nigeria. The study was guided by four research questions. The descriptive survey design was used and the population consisted of fifty-four (54) library staff in Federal Polytechnic Library, Oko, Anambra State, and forty-nine (49) library staff in Federal Polytechnic Library, Nekede, Imo State, summing up to the total number of one hundred and three (103) library staff from both tertiary institutions of study.. All one hundred and three (103) copies of questionnaires distributed were returned. The researchers adopted the entire population because the number is small and manageable as a sample size. The rating scale was the instrument used for data collection. Data collected were analyzed using simple percentages and mean scores of 2.50 midpoint based on the research questions and arranged in tables. The study revealed that library staff from both tertiary institutions study were aware of different types of security measures available and that both management should avail adequate safety measures for library resources. The study also found that the need for security measures is important to safeguard library materials, also the causes and challenges were found that better attention should be given to security in library and information services to avoid destruction of library resources. The study concluded that library staff was aware of different types of security measures available in both conventional and electronic systems, that library management has to make a positive move towards improving the security system to avoid damages or losses of library resources, and it was recommended that management of the two institutions studied should provide security systems to protect library resources from crime, installation of CCTV, RFID, video recording surveillance and other electronic measures to monitor the library space for unwanted activity or theft. Among other recommendations to ensure better safety of libraries is much needed for the two selected academic libraries, in SouthEast Nigeria.